Qualidade da dieta selecionada por bovinos na sub-região da Nhecolândia, Pantanal - Santos, Sandra Aparecida; Costa, Ciniro [UNESP]; Souza, Geraldo Da Silva; Moraes, André Steffens; Arrigoni, Mário De Beni [UNESP] (My University, 2002)
The objective of this study was to evaluate the nutritive value of the diet by cows grazing in natural pastures, in a typical area of Nhecolândia sub-region, Pantanal, during two hydrological years: from October 1997 to September 1999. Grazed forage species samples, representative of the animals' diet, were collected manually in each month. All forage samples were analyzed for crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), and lignin (LIG). Near infrared spectrofotometry (NIRS) was used to estimate the organic matter digestibility (%) indirectly from fecal samples collected monthly. There was year vs season interaction for all chemical constituents. Cows showed better body score condition from September to March of 1998/99, when the diet had average levels of 60.4%, 10%, 40.20%, 71%, and 6% for digestibility, CP, ADF, NDF and LIG, respectively. These levels appeared appropriate for meeting cow reproductive demands in the conditions of the studied area. Thus, the diet nutritive value selected by cattle is dependent on annual climatic conditions, especially the rainfall intensity and distribuiton, that cause more or less presence of water on the lowland, areas with more nutritive forage species.
Quality of the diet selected by cattle in the Nhecolândia sub-region, Pantanal
Keywords: Body condition; Nutrition; Rangelands; Reproductive performance